CLINICAL OUTCOMES OF INTRA-ARTICULAR HIGH MOLECULAR WEIGHT HYALURONIC ACID INJECTION FOR HIP OSTEOARTHRITIS- A SYSTEMATIC REVIEW AND META-ANALYSIS - Ali, Sheikh Muhammad Ebad; Farooqui, Sofia Fatima; Sahito, Badaruddin; Ali, Maratib; Khan, Ameer Ahmed; Naeem, Osama (Journal of Ayub Medical College Abbottabad, 2021)
Osteoarthritis is the most common degenerative disease of the synovial joints in the elderly population with hip osteoarthritis as the second most commonly affected joint. A multitude of conservative treatments is used for pain relief and functional improvement including acetaminophen, NSAID, intra-articular corticosteroid, and viscosupplementation (VS). Different preparations of VS based on different molecular weights are commercially available. No systematic review or meta-analysis regarding the use of intra-articular high molecular weight hyaluronic acid (HMWHA) injection for the hip joint was published before. This review analyzes the efficacy of intra-articular HMWHA for hip osteoarthritis. Methods: PubMed, Google Scholar, Cochrane Library for randomized trials describing the efficacy of HMWHA for hip osteoarthritis was searched. The search terms were osteoarthritis, hip joint, outcomes, viscosupplementation, and high molecular weight hyaluronic acid in different combinations. Standardized mean difference (SMD) in VAS for pain relief and Lequesne index for functional outcomes while risk ratio (RR) for complications was used for data pooling. Result: Four studies comprising 185 and 189 patients in HMWHA and control groups were included, respectively. SMD for VAS and Lequesne index was -0.056 and -0.114, respectively while RR for complication was 0.879. Conclusion: Intra-articular HMWHA injection provided pain relief, functional improvement, and no severe complications on immediate short term basis. However, the results do not favor treatment with HMWHA over other treatment methods. Randomized trials are further necessary to provide data regarding comparisons between HMWHA for hip osteoarthritis concerning clinicians’ convenience, compliance, duration of relief, and cost-effectiveness.